Dimensions of Nepalese Bakery Products and its Impact on Customers’ Satisfaction - Khanal, Kapil (Management Dynamics, 2020)
This research tries to identify the dimensions of Nepalese bakery products and measure the impact of Nepalese bakery products on customers’ satisfaction. This research is based on primary data. To achieve the objective, quantitative and qualitative research designs have been used. Data were collected through personal interview, questionnaire and observation with 396 customers from Kathmandu Valley. Judgmental and purposive sampling technique was used in this procedure. Demographic analysis, percentages, arithmetic means, standard deviation and multiple regression equations were used to analyze and interpret the data. It is revealed that the price of bakery products have highest mean values where as location is least important than other dimensions. Among different dimensions of bakery products, price, quality and location have significant impact upon the customers’ satisfaction under one percent level of significant. Similarly, taste of bakery items and ambience of bakery shop are significant.